Situation of Safe Motherhood: A Study of Aatharai Rural Municipality- 4, Iwa, Terhathum - Bimali, Ganesh (Intellectual Journal of Academic Research, 2023)
Safe motherhood is a critical issue in reproductive health, and the role of husbands is vital in ensuring the safety and well-being of mothers. This study aims to examine the practices of antenatal care, delivery care, and postnatal care among married men and women of reproductive age (15-49). The study utilizes primary data collected through questionnaires, supplemented with information from secondary sources.The sample size for this study consisted of 170 households, selected through snowball sampling. The criteria for inclusion in the sample were households with at least one childbirth involving both the woman and her husband. The sample areas were selected using cluster 2 and 3, determined through a lottery method.While the search results did not provide specific studies directly related to the objectives of this study, they did offer insights into related topics such as reproductive health and maternal care. For example, one study emphasized the importance of birth preparedness for clean delivery and referral, as well as newborn care. Another study highlighted the need for comprehensive sex education to mitigate teenage pregnancy. In conclusion, this study on safe motherhood and the role of husbands in reproductive health aims to shed light on the practices of antenatal care, delivery care, and postnatal care among married men and women. By examining these practices, it is hoped that strategies can be developed to improve the safety and well-being of mothers during the reproductive process.